Night of the Ninjas - Osborne, Mary Pope.; Murdocca, Sal (New York : Scholastic, 1996)
The magic tree house takes Jack and Annie back in time to feudal Japan where the siblings learn about the ways of the ninja.
"Fitzgerald Books"--Cover p. [4].
2.7
3-6
3-6
Keywords: Annie (Fictitious character : Osborne) -- Juvenile fiction; Jack (Fictitious character : Osborne) -- Juvenile fiction; Ninja -- Juvenile fiction; Time travel -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Ninja -- Fiction; Time travel -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Ninja -- Fiction; Time travel -- Fiction; Japan -- Juvenile fiction; Japan -- Fiction; Japan -- Fiction